Promoting Regulation and Flexibility in Thinking : Development of Executive Function - Weede Alexander, Kristen M.; Davis O'Hara, Karen M. (Applying child and adolescent development in the professions series, 2024)
"This concise guide introduces the importance of executive function for social and emotional well-being, and effective learning. It clearly explains the research that underpins important topics such as working memory, organization, self-regulation, attention and cognitive flexibility, and how they apply to the real-world settings in which we work with children, adolescents, and families. This engaging book offers knowledge and strategies for improving executive function together with an understanding of its relevance for diverse populations. The authors use the most current research to provide an overview of what executive function is, how it develops, and how it works in coordination with other developmental factors to promote regulation and flexibility in thinking. Chapters contain detailed information about the biological and physiological foundations for brain development and emotion regulation, as well as advances in cognition, emotion, and social relationships. Making the research accessible to all with evidence-based writing and theory-to-practice applications, the book provides applications with career contexts and interviews and case studies that bring the book to life. Designed to introduce professionals, advocates, and parents to the importance of executive function in human development, this book is for all those working with children and young people. It will also be of interest as an introductory text for those new to the field or as a way to learn to apply developmental principles in practice" --